Understanding Iran - Green, Jerrold D.; Wehrey, Frederic M.; Wolf, Charles, 1924-; National Defense Research Institute (U.S.); Rand Corporation; Smith Richardson Foundation (Santa Monica, CA : RAND, 2009)
Iran remains among the most poorly understood countries in the world and, for most Americans, terra incognita. A small community of American analysts in the government, academia, and the country's think tanks is, of course, working on Iran, but the overwhelming majority of them have never been to Iran or have visited only briefly. The consequences of this unfamiliarity have been distinctly negative for American policy, pushing most analyses toward a highly reductionist view. This monograph, the result of a workshop and the authors' own experience and analysis, is a concise, accessible handbook on the Islamic Republic for U.S. policymakers. As an aid to understanding current-day Iran, it synthesizes the existing analyses on the Islamic Republic and, most important, draws from non-American experts who can offer a different interpretive lens for viewing the seemingly opaque Iranian system. It offers a set of short analytic observations about the processes, institutions, networks, and actors that define Iran's politics, strategy, economic policy, and diplomacy. From these, it provides a guide for negotiating with Iran, about which the National Security Council's 2006 National Security Strategy warned, "We may face no greater challenge from a single country than from Iran."
Introduction -- Features of the Iranian System -- Conclusion: Iran Is Unlike Other Countries but Hardly Beyond Understanding -- Appendix A: Conclusion: Iran Is Unlike Other Countries but Hardly Beyond Understanding -- Appendix B: Workshop Papers -- Appendix C: Biographies of Workshop Participants.
Includes bibliographical references (p. 141-143).
Also available on the internet via WWW in PDF format.
Keywords: Iran -- Economic conditions -- 1997-; Iran -- Foreign relations -- 1997-; Iran -- Politics and government -- 1997-